Vivarium [videorecording (DVD)] - Finnegan, Lorcan; Shanley, Garret; Poots, Imogen, 1989-; Eisenberg, Jesse, 1983- (Lionsgate, 2020)
A couple's search for a dream home plunges them into a terrifying nightmare after they are trapped in a mysterious, labyrinth-like neighborhood of identical houses.